2010
DOI: 10.1093/annonc/mdp258
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity as prognostic variable in MDS: comparative evaluation of the HCT-CI and CCI in a core dataset of 419 patients of the Austrian MDS Study Group

Abstract: Together, our data show that comorbidity is an important risk factor for OS and EFS in patients with MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
3
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 29 publications
3
65
3
4
Order By: Relevance
“…We propose to use the MDS-CI for assessment of comorbidities in the future since it has shown its high stability in haematologica 2014; 99:e31 © F e r r a t a S t o r t i F o u n d a t i o n the hands of different study groups and has the most consistent results, 3,11 in contrast to the inconsistent results produced when using CCI and HCTCI to assess comborbidities for all MDS patients. 7,9,11,12 Furthermore, the MDS-CI is independent of the IPSS-R, as shown in our present study, and is independent of the WPSS, as shown by Breccia 8 and Della Porta 3 and co-workers. Comorbidities can be an important factor in clinical decision making.…”
supporting
confidence: 86%
“…We propose to use the MDS-CI for assessment of comorbidities in the future since it has shown its high stability in haematologica 2014; 99:e31 © F e r r a t a S t o r t i F o u n d a t i o n the hands of different study groups and has the most consistent results, 3,11 in contrast to the inconsistent results produced when using CCI and HCTCI to assess comborbidities for all MDS patients. 7,9,11,12 Furthermore, the MDS-CI is independent of the IPSS-R, as shown in our present study, and is independent of the WPSS, as shown by Breccia 8 and Della Porta 3 and co-workers. Comorbidities can be an important factor in clinical decision making.…”
supporting
confidence: 86%
“…17 Performance status and comorbidity were assessed by ECOG performance scale 18 and the hematopoietic SCT specific comorbidity index (HCT-CI), respectively. 19,20 Acute GVHD and chronic GVHD were assessed by the National Institutes of Health (NIH) Consensus Criteria. 21 …”
Section: Definitionsmentioning
confidence: 99%
“…45,47,52,58,62,[77][78][79][80][81][82][83][84] At least five other studies reported on the ability of the HCT-CI to provide good prediction of conventional treatment outcomes among patients with AML or MDS, which adds another layer to the generalizability of this index. [85][86][87][88] One study found the HCT-CI to be a sole independent predictor of outcomes among patients receiving relative or cord blood grafts, but of less strength in smaller samples of subgroup analyses. 89 Only four studies disagreed with the validity of the HCT-CI for outcome prediction.…”
Section: Validity and Reliability Of The Hct-ctmentioning
confidence: 99%